Hubungan Karakteristik Ibu Hamil Terhadap Kunjungan Antenatal Care (ANC) Di Wilayah Kerja Puskesmas Siatas Barita - Riance Mardiana Ujung; Dimpu Rismawaty Nainggolan (Jurnal Maternitas Kebidanan, 2022)
Antenatal examination is very important in an effort to reduce maternal morbidity and mortality. The estimated MMR in North Tapanuli Regency in 2016 was 139 per 100,000 live births (KH), an increase compared to 2015 which was 115 per 100,000 live births. The high AKI is caused by postpartum hemorrhage, eclampsia, sepsis and complications of miscarriage. The aims of this study to determine the relationship between knowledge of pregnant women on ANC visits. Quantitative and analytic research methods with a cross-sectional design were carried out from July to November 2019, the sample was the entire population of pregnant women who made antenatal care visits as many as 51 people. The Results of this study is from the Chi-square test there is a relationship between knowledge of pregnant women and ANC visits with a value of P = 0.000 (P < 0.05), there is a relationship between education of pregnant women and ANC visits with a value of P = 0.001 (P < 0.05), there is no relationship between the age of pregnant women and ANC visits with a value of P = 0.594 (P> 0.05), there is no relationship between parity of pregnant women and ANC visits with a value of P = 0.090 (P> 0.05), there is a relationship between occupation pregnant women with ANC visits with a value of P = 0.000 (P > 0.05). It is expected that health workers will provide more information to pregnant women about the importance of conducting antenatal care checks and improving the quality of ANC services